Cumulative Incidence of Graft Infection after Primary Prosthetic Aortic Reconstruction in the Endovascular Era. Issue 5 (May 2015) - Berger, P.; Vaartjes, I.; Moll, F.L.; De Borst, G.J.; Blankensteijn, J.D.; Bots, M.L.
<x xml:space="preserve">Abstract</x> Objective The introduction of endovascular techniques has had a major impact on the case mix of patients that undergo open aortic reconstruction. Hypothetically, this may also have increased the incidence of aortic graft infection (AGI). The aim of this study was to report on the short and mid-term incidence of AGI after primary open prosthetic aortic reconstruction in the endovascular era. Methods From 2000 to 2010, all 514 patients in a tertiary referral university hospital, undergoing primary open prosthetic aortic reconstruction for aneurysmal or occlusive aortic disease with at least one aortic anastomosis were included. Data were obtained by retrospectively analyzing the medical records, by contacting patients or their general practitioner by telephone, and by merging the dataset with the national Cause of Death Register. AGI was defined as proven by cultures or clinically in combination with positive imaging results. The 30 day, 1 year, and 2 year incidence rates were computed using life table analysis and expressed as percentages with 95% confidence intervals (CI). Results AGI was diagnosed in 23 of the 514 included patients. 56% of the patients underwent elective surgery and 86% underwent surgery for an abdominal aortic aneurysm. The 30 day incidence was 1.6% (95% CI 0.4–2.8%), 1 year incidence was 3.6% (95% CI 1.7–5.5%), and 2 year incidence for AGI was 4.5% (95% CI 2.4–6.6%). The total number of person years (1058) yielded an AGI rate of 2.2 per 100 person years. Conclusion The 2 year cumulative incidence of AGI following primary, open aortic procedures with at least one aortic anastomosis is considerable, at around 1 in 20.